Frequency control by the PV station in electric power systems with hydrogen energy storage; International Journal of Hydrogen Energy; Vol. 48, iss. 73 - Ruban N. Yu. Nikolay Yurievich; Rudnik V. E. Vladimir Evgenevich; Askarov A. B. Alisher Bakhramzhonovich; Malyuta (Maliuta) B. D. Boris Dmitrievich (2023, 2023)
Title screen